Job satisfaction and its relationship to the psychological happiness of teachers in schools of talent and ordinary -A field study in the cities of Tartous and Lattakia - Slimoon , Reem; Sultan, Manal; Sleiman , Hala (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The aim of the research is to identify the level of job satisfaction of teachers in the schools of talent and ordinary in the cities of Tartous and Lattakia, as well as the level of their psychological happiness, and the relationship between job satisfaction and psychological happiness among the research sample of teachers, as well as the difference between teachers in the level of job satisfaction, and the level of psychological happiness they have depending on the variables (school type, educational experience, city). In order to achieve the objective of the research, the descriptive analytical method was used. The sample included 254 teachers from schools of talent and ordinary in the cities of Tartous and Lattakia for the academic year 2017/2018. Two measures were applied. The first (job satisfaction scale), included 24 clauses, and the second, (Psychological Happiness Scale) included 28 clauses. And reached several results, the most important of them: - The level of job satisfaction of teachers in the schools of talent and ordinary came to a medium degree - The level of psychological happiness of teachers in the schools of talent and ordinary came to a medium degree. - There is a significant statistical correlation between the level of job satisfaction and the level of psychological happiness among the members of the research sample of teachers in the schools of talent and ordinary in the cities of Tartous and Lattakia. - There is a statistically significant difference among the sample of teachers in the level of job satisfaction, as well as in the level of psychological happiness according to the variables (type of school), in favor of schools of talent. - There were no statistically significant differences at the level of significance (0.05) among the sample of teachers in the level of job satisfaction, as well as in the level of psychological happiness according to the variable (educational experience). - There was no statistically significant difference at the level of significance (0.05) among the sample of teachers in the level of job satisfaction, as well as in the level of psychological happiness according to the variable (city).